1999
DOI: 10.1007/pl00012371
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Common Bile Duct Exploration

Abstract: Since the introduction of laparoscopic cholecystectomy, the management of common bile duct (CBD) stones has undergone significant change. Preoperative endoscopic retrograde cholangiopancreatography (ERCP) with sphincterotomy is now routinely done in cases where the diagnosis of choledocholithiasis is suspected preoperatively, with clearance of the bile ducts before laparoscopic cholecystectomy. Intraoperative discovery of CBD stones by cholangiography represents a challenge to the surgeon, who must make a deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 22 publications
(26 reference statements)
4
14
0
Order By: Relevance
“…The clearance rate for CBDS in the present study was 100 % in both the groups which is one of the best reported in the literature [11,26,31,47,48]. This has been possible due to the meticulous attention to detail paid by the authors in checking residual stones in the CBD using IOC or check choledochoscopy, as the case may be, in all the patients.…”
Section: Discussionsupporting
confidence: 57%
“…The clearance rate for CBDS in the present study was 100 % in both the groups which is one of the best reported in the literature [11,26,31,47,48]. This has been possible due to the meticulous attention to detail paid by the authors in checking residual stones in the CBD using IOC or check choledochoscopy, as the case may be, in all the patients.…”
Section: Discussionsupporting
confidence: 57%
“…LCBDE has been performed in 2-12.1% of laparoscopic cholecystectomies [4,33,35,38,42,45]. The most common laparoscopic approach (Table 1) for common bile duct exploration has been the transcystic, and in 24 of the 31 reported series, the laparoscopic transcystic approach was the preferred method.…”
Section: Resultsmentioning
confidence: 96%
“…For ERCP ± ES, the stone clearance rates are 65-75% after one session and increase to 85-92.5% after three sessions [12]. The success rates decrease in patients with altered anatomy, such as intradiverticular papilla, abnormal localization of papilla, retropancreatic stenosis of bile duct, Billroth II bypass, and Mirizzi syndrome [23,24]. ERCP ± ES has a morbidity of 7.6-13.5% and includes the risk of pancreatitis, bleeding, perforation, cholangitis, delayed stricture of sphincter, residual/recurrent stones, papillary stenosis, and mortality of 0.4-0.55% [14,16].…”
Section: Discussionmentioning
confidence: 99%